Vulnerability or resilience to early substance use among adolescents at risk: The roles of maltreatment and father involvement - Yoon, Susan (Child Abuse Negl, 2018)
Although research has indicated that maltreated children are at higher risk of adolescent substance use, it remains unclear whether the type and timing of maltreatment affect the likelihood of adolescent substance use. Research has also found father involvement to be a potential protective factor against adolescent substance use, but the role of quality vs. quantity of father involvement as well as gender differences in the effects of father involvement on substance use among at-risk adolescents have not been studied. The current study adds value to the existing literature by filling these gaps in knowledge. We conducted a secondary data analysis with a sample of 685 at-risk adolescents drawn from the Longitudinal Studies of Child Abuse and Neglect. The study found a connection between early childhood (birth to 5) physical abuse and adolescent substance use, but not for later childhood physical abuse or other forms of child maltreatment. The quality of father involvement was found to be a protective factor, regardless of child gender; quantity of father involvement was not significant. Based on these findings, development of intervention strategies focusing on prevention of early childhood physical abuse and promoting positive father-child relationships are important prevention strategies for adolescent substance use. Additionally, professionals working with at-risk adolescents need to be cognizant of the implications of early childhood physical abuse and act accordingly to mitigate the increased potential for adolescent substance use.